2003
DOI: 10.1089/088922203769232557
|View full text |Cite
|
Sign up to set email alerts
|

Microglia from Mice Transgenic for a Provirus Encoding a Monocyte-Tropic HIV Type 1 Isolate Produce Infectious Virus and Displayin Vitroandin VivoUpregulation of Lipopolysaccharide-Induced Chemokine Gene Expression

Abstract: A large body of evidence has indicated that microglia are the predominant cellular location for HIV-1 in the brains of HIV-1-infected individuals and play a direct role in the development of HIV-1-associated dementia (HAD). Therefore, investigation of the mechanism by which HIV-1-infected microglia contribute to the development of HIV-associated dementia should be facilitated by the creation of a mouse model wherein microglia carry replication-competent HIV-1. To circumvent the inability of HIV-1 to infect mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…These mice are transgenic for an infectious full-length HIV-1 provirus derived from the well-characterized primary R5-tropic clinical isolate HIV-1 JR-CSF that is under the control of the endogenous HIV-1 LTR, and their T lymphocytes and monocytes produce infectious HIV-1 and display plasma viremia of up to 10 5 HIV copies/ml (10, 51). The LTR-regulated HIV-1 transgene is expressed in the brains and microglia of JR-CSF mice and is responsive to in vivo and in vitro LPS stimulation, and its expression is associated with increased in vivo and in vitro CCL2/MCP-1 gene expression in response to LPS (75). HIV-1 proviral expression and virus production in the JR-CSF transgenic mouse model still were limited by the inability of Tat to function as a transcriptional activator in mouse cells (7,21,22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These mice are transgenic for an infectious full-length HIV-1 provirus derived from the well-characterized primary R5-tropic clinical isolate HIV-1 JR-CSF that is under the control of the endogenous HIV-1 LTR, and their T lymphocytes and monocytes produce infectious HIV-1 and display plasma viremia of up to 10 5 HIV copies/ml (10, 51). The LTR-regulated HIV-1 transgene is expressed in the brains and microglia of JR-CSF mice and is responsive to in vivo and in vitro LPS stimulation, and its expression is associated with increased in vivo and in vitro CCL2/MCP-1 gene expression in response to LPS (75). HIV-1 proviral expression and virus production in the JR-CSF transgenic mouse model still were limited by the inability of Tat to function as a transcriptional activator in mouse cells (7,21,22).…”
Section: Discussionmentioning
confidence: 99%
“…To develop an in vivo model for studying the pathogenesis of HIV infection, we circumvented the entry block of HIV into mouse cells by developing transgenic mice that carry an integrated full-length infectious HIV-1 provirus derived from the primary R5-tropic clinical isolate HIV-1 JR-CSF that is under the control of the endogenous HIV-1 long terminal repeat (LTR) (JR-CSF mice); JR-CSF mice are populated with T lymphocytes and monocytes that produce infectious HIV-1 and display plasma viremia of up to 10 5 HIV copies/ml (10,51). The LTR-regulated HIV-1 transgene is expressed in the brains and microglia of JR-CSF mice and is responsive to in vivo and in vitro LPS stimulation, and its expression is associated with increased in vivo and in vitro CCL2/monocyte chemoattractant protein (MCP-1) gene expression in response to LPS (75). HIV production in this HIV transgenic model was increased by the coexpression of a transgene encoding hu-cycT1 under the control of a CD4 promoter.…”
mentioning
confidence: 99%
“…JR-CSF mice are transgenic for a full-length HIV-1 provirus that is expressed in the spleens, lymph nodes, thymuses, and brains of JR-CSF mice, and JR-CSF mouse T lymphocytes, monocytes, and microglia produce infectious HIV-1 (8,47,64). JR-CSF mouse splenocytes express Tat mRNA (data not shown), as determined by analysis using RT-PCR as described previously (31).…”
Section: Transgenic Expression Of Human Cyclin T1 Increases Hiv-1 Promentioning
confidence: 91%
“…HIV-1 infection of monocytes may induce chemokine production that facilitates the spread of infection by inappropriate induction of migration of T lymphocytes and inflammatory cells to the infected cells (62). We had previously demonstrated that MCP-1 gene expression in JR-CSF mouse microglia and brains was more responsive to in vitro and in vivo stimulation with LPS than that in microglia and brains from control mice (64). Therefore, we examined whether expression of the integrated HIV-1 provirus also affects chemokine production by stimulated JR-CSF bone marrow-derived mouse myeloid cells and whether Tat-mediated transactivation contributes to dysregulation of the chemokine response.…”
Section: Fig 4 Human Cyclin T1 Expression Increases the Infectiousnmentioning
confidence: 99%
“…Furthermore, infectious HIV-1 is produced by monocytes and microglia from the JR-CSF mice, and LPS-stimulated JR-CSF mouse monocytes and microglia produce higher levels of MCP-1 than monocytes and microglia from LPS-stimulated control mice (65). Because JR-CSF mouse monocytes and microglia carry an HIV-1 provirus regulated by the HIV-1 long terminal repeat, we used this model to investigate whether HIV-1 infection of monocytes increases their in vivo capacity to cross the intact and LPS-compromised BBB and migrate into the brain.…”
mentioning
confidence: 98%